Cover film
By using cellulose triacetate derived from wood pulp as a support and using a specific polymer composition in the polymer layer, the problem of insufficient adhesion between the cover film and the substrate bond is solved, and better adhesion and long-term stability are achieved.
Patent Information
- Application Number
- CN202380065770.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-09-05
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the adhesion between the covering film and the substrate during long-term storage is insufficient, and there is room for improvement.
A polymer of specific composition, such as acrylic resin and polyester resin, is used to meet certain xylene residue and glass transition temperature requirements, are used in the polymer layer.
The adhesion between the cover film and the substrate is improved, and especially under long-term storage conditions, it maintains a high adhesion and stability.
Smart Images

Figure BDA0005309490450000231 
Figure BDA0005309490450000271
Abstract
Description
Technical Field
[0001] The invention relates to a covering film. Background Art
[0002] In the field of medical cell diagnosis and tissue diagnosis, there is a known method of observing a specimen for microscopic observation using a microscope. As a method for preparing the above-mentioned specimen for microscopic observation, for example, the following method can be cited: using an automatic sealing device, a covering film having a polymer (e.g., an adhesive and a compound that can be an adhesive, etc.) pre-formed on a support is automatically overlapped on a substrate (e.g., a glass slide, etc.) to which a few drops of a solvent (hereinafter, also referred to as "sealing liquid") that can swell and / or dissolve the above-mentioned polymer are added and on which a test object is placed, so that the covering film and the substrate are bonded (hereinafter, also referred to as "sealing"). By this method, a specimen for microscopic observation in which the test object is fixed between the substrate and the covering film can be prepared.
[0003] For example, Patent Document 1 describes a transparent coating film comprising: a support comprising cellulose triacetate whose raw material is cotton linters; and a coating layer obtained by applying a coating solution comprising at least two solvents, an acrylic copolymer, a cellulose derivative, and a plasticizer.
[0004] Previous technical literature
[0005] Patent Literature
[0006] Patent Document 1: U.S. Patent No. 10,988,590 Summary of the invention
[0007] Technical issues to be solved by the invention
[0008] The present inventors, with reference to Patent Document 1, studied the performance of a covering film having a support and a polymer layer, and found the following: depending on the structure of the support and the polymer layer, there is room for further improvement in the adhesion between the substrate and the polymer layer when the covering film and the substrate are bonded together to obtain a bonded body for long-term storage.
[0009] An object of the present invention is to provide a cover film having better adhesion to a substrate when a laminate of the cover film and the substrate is stored for a long period of time.
[0010] Means for solving technical problems
[0011] The present inventors have conducted intensive studies on the above-mentioned problems and have found that the above-mentioned problems can be solved by the following structure.
[0012] [1] A cover film comprising a support and a polymer layer containing a polymer, wherein the support contains cellulose triacetate derived from wood pulp, and the polymer layer satisfies requirement 1 described below.
[0013] [2] The cover film according to [1], wherein the polymer includes at least one polymer A selected from the group consisting of acrylic resins and polyester resins.
[0014] [3] The cover film according to [1] or [2], wherein the polymer comprises an acrylic resin having repeating units derived from two or more monomers selected from the group consisting of acrylic acid ester monomers and methacrylic acid ester monomers.
[0015] [4] The cover film according to [2] or [3], wherein the weight average molecular weight of the acrylic resin is 50,000 to 150,000.
[0016] [5] The cover film according to any one of [1] to [4], wherein the polymer layer has a glass transition temperature of 35° C. or higher.
[0017] [6] The covering film according to any one of [1] to [5], wherein the polymer comprises a Hansen solubility parameter distance with xylene of 8 MPa. 0.5 Polymer B1 above.
[0018] [7] The cover film according to [6], wherein the polymer B1 includes at least one selected from the group consisting of a polymer having a polyoxyalkylene chain, a polymer having a polyalkyleneimine chain, a polymer having a cyclic amide group, and cellulose acetate.
[0019] [8] The cover film according to any one of [1] to [5], wherein the polymer includes a polymer B2 having a cross-linked structure.
[0020] [9] The cover film according to any one of [1] to [8], wherein the polymer layer further contains a plasticizer.
[0021]
[10] The covering film according to any one of [1] to [9], which is used to cover an object to be measured on a substrate during microscopic observation.
[0022] Effects of the Invention
[0023] According to the present invention, it is possible to provide a cover film having more excellent adhesion to a substrate when a laminate of the cover film and the substrate is stored for a long period of time. DETAILED DESCRIPTION
[0024] Hereinafter, the present invention will be described in detail.
[0025] In addition, although the description of the components according to the embodiments of the present invention may be made based on representative embodiments of the present invention, the present invention is not limited to such embodiments.
[0026] In this specification, the numerical range represented by "~" indicates a range that includes the numerical values recorded before and after "~" as the minimum value and the maximum value, respectively. In the numerical range recorded in stages in this specification, the upper limit value or lower limit value recorded in a certain numerical range can be replaced by the upper limit value or lower limit value of the numerical range recorded in other stages. Furthermore, in the numerical range recorded in this specification, the upper limit value or lower limit value recorded in a certain numerical range can also be replaced by the value shown in the embodiment.
[0027] In the present specification, a combination of two or more preferred aspects is a more preferred aspect.
[0028] In the present specification, when a plurality of substances corresponding to each component are present in a composition or a layer, the amount of each component in the composition or the layer refers to the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0029] In this specification, "(meth)acrylic acid" is a general term for acrylic acid and methacrylic acid, and means "one or more of acrylic acid and methacrylic acid". Similarly, "(meth)acrylate" means "one or more of acrylate and methacrylate", "(meth)acryloyl" means "one or more of acryloyl and methacryloyl", and "acrylic resin" means "a polymer having one or more repeating units derived from an acrylate monomer and / or a methacrylate monomer".
[0030] In this specification, unless otherwise specified, the refractive index refers to a refractive index with respect to light having a wavelength of 550 nm measured using an Abbe refractometer ("NAR-2T" manufactured by ATAGO CO., LTD.).
[0031] In this specification, unless otherwise specified, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are molecular weights obtained as follows: by using a gel permeation chromatography (GPC: Gel Permeation Chromatography) analysis apparatus using a TSKgel GMHxL, TSKgel G4000HxL, TSKgel G2000HxL and / or TSKgelSuper HZM-N (all trade names manufactured by Tosoh Corporation) column, using THF (tetrahydrofuran) as a solvent, detecting by a differential refractometer, and converting using polystyrene as a standard substance.
[0032] [Cover film]
[0033] The cover film of the present invention comprises a support and a polymer layer comprising a polymer, wherein the support comprises cellulose triacetate derived from wood pulp.
[0034] Furthermore, the polymer layer included in the cover film of the present invention satisfies the following requirement 1.
[0035] Requirement 1: The remaining ratio of the polymer layer before and after the polymer layer peeled off from the cover film is immersed in xylene at 25° C. is 10 to 50% by mass.
[0036] In the cover film of the present invention, the support contains cellulose triacetate derived from wood pulp, and the polymer layer satisfies the above-mentioned requirement 1. The detailed mechanism by which the adhesion between the cover film and the substrate is improved when the laminate of the cover film and the substrate is stored for a long period of time is not yet clear, but the present inventors speculate as follows.
[0037] It is believed that when the residual rate of the polymer layer is 10% by mass or more, in the laminate obtained by laminating the cover film and the substrate using the sealing liquid, the component having the property of being difficult to dissolve in xylene in the above-mentioned immersion test and the triacetyl cellulose derived from wood pulp constituting the support body are appropriately entangled to exert excellent adhesion, and the adhesion is maintained even if the laminate is stored for a long time. In particular, it is believed that the above-mentioned adhesion is excellent because the molecular structure of the triacetyl cellulose derived from wood pulp is not uniform. On the other hand, it is believed that when the residual rate of the polymer layer is 50% by mass or less, the polymer layer is appropriately dissolved when the laminate is produced, thereby improving the adhesion between the cover film and the substrate after long-term storage.
[0038] In this specification, "the effect of the present invention" refers to the adhesion between the cover film and the substrate when a laminated body in which the cover film and the substrate are laminated is stored for a long period of time.
[0039] Next, the structure of the cover film will be described.
[0040] 〔Support〕
[0041] The support contains triacetyl cellulose (hereinafter also referred to as “specific TAC”) derived from wood pulp. Wood pulp is pulp obtained by steaming wood such as broadleaf trees and coniferous trees by a known method, and specific TAC is triacetyl cellulose produced using wood pulp as a raw material.
[0042] As the support, a support composed of specific TAC is preferred.
[0043] Specific TAC can be identified by the constituent sugars of hemicellulose contained in cellulose triacetate. More specifically, when the ratio of the total molar amount of mannose and xylose in the constituent sugars of cellulose triacetate to the total molar amount of the constituent sugars contained in cellulose triacetate {(total molar amount of mannose and xylose) / (total molar amount of constituent sugars of cellulose triacetate)} is 0.5% or more, the cellulose triacetate can be determined to be specific TAC. On the other hand, when the above ratio is less than 0.5%, the cellulose triacetate can be determined to be derived from cotton linters.
[0044] The molar amount of constituent sugars contained in cellulose triacetate can be analyzed according to the method described in Japanese Patent Application Laid-Open No. 2005-82744.
[0045] The degree of substitution of the acetyl group in the specific TAC is, for example, 2.50 to 3.00, or preferably 2.80 to 2.95.
[0046] Examples of a method for measuring the degree of substitution include known measurement methods such as FT-IR method and titration method.
[0047] The weight average molecular weight (Mw) of the specific TAC contained in the support is, for example, 10,000 to 1,000,000, or preferably 30,000 to 300,000.
[0048] The method for producing specific TAC is not particularly limited, and it can be produced, for example, by a known method in which wood pulp is activated with acetic acid or the like, triacetate is prepared with acetic anhydride using a sulfuric acid catalyst, and the substitution degree is adjusted by saponification (hydrolysis).
[0049] The support preferably contains specific TAC as a main component. The "main component" refers to the component with the largest content among the components contained in the support.
[0050] The content of the specific TAC contained in the support is preferably more than 50% by mass, more preferably 80% by mass or more, relative to the total mass of the support. The upper limit is not particularly limited, and may be 100% by mass or less relative to the total mass of the support.
[0051] The support may comprise other materials besides the specific TAC.
[0052] As other materials contained in the support, known materials used in the support of the covering film can be used, for example, cellulose polymers such as cellulose diacetate, cellulose acetate propionate and cellulose acetate butyrate (except specific TAC); polyester polymers such as aliphatic polyesters; polyolefin polymers such as cycloolefin polymer (COP), polyethylene and polypropylene; acrylic resins; polycarbonate (PC); and polystyrene.
[0053] The support may contain additives.
[0054] Examples of the additives include a retardation control agent, a degradation inhibitor, an ultraviolet light inhibitor, a peeling accelerator, a plasticizer, an infrared absorber, and a matting agent.
[0055] In the case where the support contains other resins and / or additives other than the specific TAC, the total content thereof may be the remainder of the specific TAC.
[0056] <Physical properties of support>
[0057] The thickness of the support is not particularly limited, but is preferably 50 to 250 μm, more preferably 50 to 150 μm, and further preferably 100 to 150 μm.
[0058] The refractive index of the support is not particularly limited, but may be, for example, 1.44 to 1.60, and is preferably 1.46 to 1.56, which is close to a slide glass (refractive index 1.52 to 1.56), from the viewpoint of better visibility when bonded to a substrate.
[0059] From the viewpoint of better visibility when attached to the substrate, the support is preferably a transparent support. In addition, in this specification, "transparent" means that the transmittance of visible light (wavelength: 380 to 780 nm) is 60% or more. The transmittance is the ratio of the transmitted light to the incident light of the support.
[0060] The support can be produced from a raw material containing specific TAC by a known film forming method such as solution film forming and melt film forming.
[0061] The support may be subjected to surface treatment such as ultraviolet irradiation, corona discharge, or glow discharge.
[0062] 〔Polymer layer〕
[0063] The cover film contains a polymer and has a polymer layer satisfying the above-mentioned requirement 1.
[0064] Whether the polymer layer satisfies requirement 1, that is, whether the residual rate of the polymer layer before and after immersing the polymer layer peeled from the cover film in xylene at 25° C. (hereinafter also referred to as “xylene residual rate”) is 10 to 50% by mass, is confirmed by the following method.
[0065] The polymer layer is peeled off from the covering film, and the polymer layer is cut to an area equivalent to a circle with a diameter of 20 mm to obtain a sample of the polymer layer. The obtained sample is immersed in 2 g of xylene (temperature 25° C.). After immersion for a sufficient time (for example, more than 4 hours), the residue insoluble in xylene is taken out, and xylene is completely removed from the residue by drying. Based on the weight of the sample before immersion and the weight of the residue after immersion, the xylene residual rate (mass %) is calculated by the following formula.
[0066] Xylene residual rate = {(weight of sample before immersion - weight of residue after immersion) / weight of sample before immersion} × 100
[0067] In addition, xylene is a representative solvent used in the encapsulation, but even if the solvent used in the encapsulation is a solvent other than xylene, as long as the support contains a specific TAC and the xylene residual rate is within the above range, the adhesion between the laminate and the substrate can be achieved during long-term storage, thereby solving the problem of the present invention.
[0068] From the viewpoint of further improving the effect of the present invention, the residual xylene ratio is preferably 15 to 40% by mass, more preferably 28 to 37% by mass.
[0069] The xylene residual ratio of the polymer layer can be adjusted by changing the types and contents of the components contained in the polymer layer.
[0070] <Polymer>
[0071] The polymer constituting the polymer layer is not particularly limited as long as the polymer layer satisfies requirement 1. The polymer constituting the polymer layer preferably swells in an organic solvent (especially xylene) used as a sealing liquid in an automatic sealing device, and more preferably dissolves in the above organic solvent.
[0072] Examples of organic solvents used as sealing liquids in the automatic sealing device include xylene, toluene, mesitylene (1,3,5-trimethylbenzene), pseudocumene (1,2,4-trimethylbenzene), mesitylene (1,2,3-trimethylbenzene), durene (1,2,4,5-tetramethylbenzene), 3-methylbutyl acetate, anisole, ethyl propionate, amyl acetate, propyl acetate, isopropyl acetate, butyl acetate, methyl lactate, dimethyl carbonate, 1-butanol, Any one of 1-propanol, 2-butanol, 1-pentanol, 2-pentanol, isopentanol, tert-pentanol, neopentyl alcohol, cyclopentanol, 2-hexanol, 4-methyl 2-pentanol, methyl isobutyl ketone, acetylacetone, cyclopentanone, n-butyl ether, 1,2-dimethoxyethane, dioxane, cyclopentyl methyl ether, 1-methoxy-2-propanol, propylene glycol methyl ether acetate, ethyl acetate, methyl acetate, acetone and methyl ethyl ketone, and a mixed solvent of two or more thereof.
[0073] The polymer constituting the polymer layer swells or dissolves in the organic solvent, whereby the cover film and the substrate are bonded (a bonding portion is formed), and the object to be measured can be enclosed.
[0074] (Polymer A)
[0075] From the viewpoint of excellent solubility in organic solvents (especially xylene), the polymer constituting the polymer layer preferably includes at least one polymer selected from the group consisting of acrylic resins and polyester resins (hereinafter also referred to as "polymer A"), and more preferably includes an acrylic resin.
[0076] In addition, the components and composition of the polymer contained in the polymer layer are determined by using 1 The molecular weight can be obtained by measuring a sample of the polymer layer collected from the cover film using a known method such as H-NMR (nuclear magnetic resonance) and GPC (gel permeation chromatography).
[0077] -Acrylic resin-
[0078] Examples of acrylic resins include polymers having repeating units derived from acrylate monomers and / or methacrylate monomers. The acrylic resin may be a homopolymer of one monomer selected from the group consisting of acrylate monomers and methacrylate monomers, or a copolymer of two or more monomers selected from the group consisting of acrylate monomers and methacrylate monomers.
[0079] Among them, acrylic resins having two or more repeating units derived from monomers selected from the group consisting of acrylic acid ester monomers and methacrylic acid ester monomers are preferred from the viewpoint of having better adhesiveness after being dissolved in an encapsulating solvent such as xylene.
[0080] Furthermore, the acrylic resin may be a copolymer of one or more monomers selected from the group consisting of acrylate monomers and methacrylate monomers and one or more monomers other than acrylate monomers and methacrylate monomers (e.g., acrylamide monomers such as dimethylacrylamide and isopropylacrylamide, and vinyl monomers such as styrene).
[0081] Furthermore, the acrylic resin preferably does not have a cross-linked structure described below.
[0082] In the acrylic resin, the total content of repeating units derived from acrylate monomers and methacrylate monomers is preferably 50% by mass or more, more preferably 70% by mass or more, and further preferably 90% by mass or more relative to all repeating units of the acrylic resin. The upper limit of the total content of repeating units derived from acrylate monomers and methacrylate monomers is not particularly limited and may be 100% by mass relative to all repeating units of the acrylic resin.
[0083] The acrylic resin is particularly preferably one having only repeating units derived from an acrylic acid ester monomer and / or a methacrylic acid ester monomer.
[0084] Examples of the acrylic acid ester monomer and the methacrylic acid ester monomer include acrylic acid alkyl ester and methacrylic acid alkyl ester.
[0085] The alkyl group in the alkyl acrylate and alkyl methacrylate may be linear or branched. The alkyl group may further have a substituent. Examples of the substituent include an aryl group and a hydroxyl group, preferably an aryl group, and more preferably a phenyl group. The number of carbon atoms in the alkyl acrylate and alkyl methacrylate that may have a substituent is preferably 1 to 15, more preferably 1 to 8, further preferably 1 to 5, and particularly preferably 1 to 3.
[0086] Specific examples of the above-mentioned alkyl acrylate monomers include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, lauryl acrylate, phenyl acrylate, benzyl acrylate, 2-methoxyethyl methacrylate, hydroxyethyl acrylate and acetoacetoxyalkyl acrylate.
[0087] Specific examples of the alkyl methacrylate monomer include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, benzyl methacrylate, lauryl methacrylate, 2-methoxyethyl methacrylate, hydroxyethyl methacrylate and acetoacetoxyalkyl methacrylate.
[0088] The acrylic resin is most preferably an acrylic resin containing repeating units derived from ethyl acrylate, repeating units derived from methyl methacrylate, and repeating units derived from other methacrylic acid alkyl esters other than methyl methacrylate. Examples of the other methacrylic acid alkyl esters include ethyl methacrylate.
[0089] The acrylic resin can be synthesized by a known method such as polymerizing one or more monomers selected from the group consisting of acrylic acid ester monomers and methacrylic acid ester monomers.
[0090] The weight average molecular weight (Mw) of the acrylic resin is preferably 10,000 to 500,000, more preferably 50,000 to 150,000, and further preferably 60,000 to 120,000.
[0091] -Polyester resin-
[0092] Examples of the polyester resin include polyesters obtained by polycondensation of dicarboxylic acid and diol.
[0093] The polyester resin is more preferably a polycondensation polyester obtained from at least one dicarboxylic acid having an aromatic ring (aromatic dicarboxylic acid) and at least one diol, that is, more preferably a polycondensation polyester containing at least one aromatic dicarboxylic acid residue and at least one diol residue.
[0094] Here, the residue refers to a partial structure of the polyester resin, and indicates a partial structure derived from a monomer used to form the polyester resin. For example, a dicarboxylic acid residue formed from a dicarboxylic acid "HOOC-R-COOH (R represents a hydrocarbon group)" is "-OC-R-CO-".
[0095] Furthermore, the polyester resin preferably does not have a cross-linked structure described below.
[0096] Examples of the aromatic dicarboxylic acid include phthalic acid, terephthalic acid, isophthalic acid, 1,5-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 2,8-naphthalene dicarboxylic acid, and 2,6-naphthalene dicarboxylic acid. Among them, phthalic acid, terephthalic acid, or isophthalic acid is preferred, phthalic acid or terephthalic acid is more preferred, and terephthalic acid is further preferred.
[0097] The aromatic dicarboxylic acid for forming the aromatic dicarboxylic acid residue may be one kind alone or two or more kinds thereof.
[0098] The polyester resin may contain an aliphatic dicarboxylic acid residue in addition to the aromatic dicarboxylic acid residue.
[0099] Examples of the aliphatic dicarboxylic acid include oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid.
[0100] The aliphatic dicarboxylic acid for forming the aliphatic dicarboxylic acid residue may be one kind alone or two or more kinds.
[0101] Examples of the diol used for forming the polyester resin include aromatic diols and aliphatic diols.
[0102] The polyester resin preferably contains an aliphatic diol residue. For example, a diol residue formed from diol "HO-R-OH" is "-ORO-".
[0103] Examples of the aliphatic diol for forming the aliphatic diol residue include alkyl diol and alicyclic diol. More specifically, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2-methyl-1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 2,2-dimethyl-1,3-propylene glycol (neopentyl glycol), 2,2-diethyl-1,3-propylene glycol (3,3-dimethylpentane), 2-n-butyl-2-ethyl-1,3-propylene glycol (3,3-dimethylolheptane), 3-methyl-1,5-pentanediol, 1,6-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-octadecanediol, diethylene glycol, and cyclohexanedimethanol can be mentioned.
[0104] As the aliphatic diol, ethylene glycol, 1,2-propylene glycol or 1,3-propylene glycol is preferred, and ethylene glycol or 1,2-propylene glycol is more preferred.
[0105] The aliphatic diol used for forming the aliphatic diol residue may be one kind alone or two or more kinds thereof.
[0106] The terminal of the polyester resin may be in an unsealed state or in a sealed state, but is preferably sealed by reacting a monocarboxylic acid or a monoalcohol with a terminal group of a hydroxyl group or a carboxyl group.
[0107] The monocarboxylic acid used for terminal sealing is preferably acetic acid, propionic acid, butyric acid or benzoic acid, more preferably acetic acid or propionic acid, and further preferably acetic acid. The monoalcohol used for terminal sealing is preferably methanol, ethanol, propanol, isopropanol, butanol or isobutanol, and more preferably methanol.
[0108] The terminal group of the polyester resin is preferably an acyl group, an alkoxy group, or an aryloxy group, and more preferably an acetyl group or a propionyl group.
[0109] The polyester resin can be synthesized by a known method such as a hot melt condensation method of polycondensing a diol and a dicarboxylic acid and an interfacial condensation method of a dicarboxylic acid chloride and a diol.
[0110] The polymer A may be used alone or in combination of two or more. When two or more polymers A are used, they are preferably used in such a ratio that a dried film obtained by mixing the two or more polymers A does not become turbid.
[0111] The content of the polymer A in the polymer layer is not particularly limited, but is preferably 50 to 80% by mass, more preferably 60 to 70% by mass, based on the total mass of the polymer layer.
[0112] (Polymer B)
[0113] The polymer layer may contain other polymers besides the above-mentioned polymer A.
[0114] As other polymers other than polymer A, for example, polymers having a Hansen solubility parameter distance of 5 MPa from xylene can be mentioned. 0.5 The above polymer B1 and polymer B2 have a cross-linked structure.
[0115] From the viewpoint of achieving more excellent effects of the present invention, the polymer layer preferably contains, in addition to the polymer A, at least one polymer selected from the group consisting of polymers B1 and B2 (hereinafter also referred to as “polymer B”).
[0116] -Polymer B1-
[0117] The polymer layer preferably includes, in addition to the polymer A, a polymer having a Hansen solubility parameter distance (hereinafter also referred to as "ΔHSP") with xylene of 5 MPa. 0.5 Polymer B1 above.
[0118] As polymer B1, the ΔHSP with xylene is preferably 8 MPa. 0.5 The above polymers preferably have a ΔHSP of 10 MPa with xylene. 0.5 The upper limit of the ΔHSP is not limited, for example, it can be 40 MPa. 0.5 the following.
[0119] Hansen solubility parameters (HSP) divide the solubility of a substance into three components (dispersion term δD, polar term δP, and hydrogen bonding term δH) and represent them in three-dimensional space. The dispersion term δD represents the effect based on dispersion force, the polar term δP represents the effect based on dipole force, and the hydrogen bonding term δH represents the effect of hydrogen bonding force.
[0120] The Hansen solubility parameter distance (ΔHSP) of the polymer to xylene was calculated by the following formula (D).
[0121] Formula (D) ΔHSP = (4 × (dDa-dDb) 2 +(dPa-dPb) 2 +(dHa-dHb) 2 ) 0.5
[0122] dDa: Dispersion term of polymer (unit: MPa 0.5 )
[0123] dPa: Polarization term of polymer (unit: MPa 0.5 )
[0124] dHa: Hydrogen bonding term of polymer (unit: MPa 0.5 )
[0125] dDb: Dispersion term of xylene (unit: MPa 0.5 )
[0126] dPb: polarization term of xylene (unit: MPa 0.5 )
[0127] dHb: Hydrogen bonding term of xylene (unit: MPa 0.5 )
[0128] In addition, the values of the dispersion term, polarization term, and hydrogen bonding term of the polymer are determined based on the composition of the polymer identified by a known method.
[0129] When the polymer is composed of two or more repeating units, the above δDa, δPa and δHa are respectively calculated by multiplying the dispersion term, polar term or hydrogen bonding term of each repeating unit by the mass content of each repeating unit. In addition, the Hansen solubility parameter of the monomer inducing the repeating unit constituting the polymer may be used instead of the Hansen solubility parameter of the repeating unit.
[0130] The definition and calculation method of the Hansen solubility parameters of each compound are described in Hansen Solubility Parameters: A Users Handbook by Charles M. Hansen (CRC Press, 2007). In addition, by using the computer software Hansen Solubility Parameters in Practice (HSPiP), the Hansen solubility parameters of unknown compounds such as literature values can be easily estimated from their chemical structures.
[0131] In this specification, regarding the Hansen solubility parameters including ΔHSP, HSPiP (ver. 5) is used and the values calculated according to the Y-MB method are used.
[0132] Examples of polymer B1 having a ΔHSP within the above range include polymers having a polyoxyalkylene chain, polymers having a polyethyleneimine chain, polymers having a cyclic amide group, and cellulose acetate. Preferably, the polymers having a polyoxyalkylene chain, polymers having a cyclic amide group, or cellulose acetate are mentioned.
[0133] The polymer having a polyoxyalkylene chain is a high molecular compound having a polyoxyalkylene chain having repeating oxyalkylene groups in at least one of a main chain and a side chain.
[0134] Examples of the alkylene group constituting the polyoxyalkylene chain include linear or branched alkylene groups having 1 to 6 carbon atoms, and an ethylene group, a propylene group, or a butylene group is preferred.
[0135] The oxyalkylene groups constituting the polyoxyalkylene chain may be a single type or two or more types. When the polyoxyalkylene chain has two or more types of oxyalkylene groups, it may be a block polymer of the two or more types of oxyalkylene groups or a random polymer.
[0136] Examples of the polymer having a polyoxyalkylene chain in the main chain include polyethylene glycol, polyethylene glycol with an amino terminal, polypropylene glycol, polypropylene glycol with an amino terminal, polybutylene glycol, and polybutylene glycol with an amino terminal.
[0137] In the polymer having a polyoxyalkylene chain in a side chain, the structure of the main chain is not particularly limited, and examples thereof include polyurethane, polystyrene, polyester, polyamide, polyimide, and polyurea, and polyurethane is preferred.
[0138] The number of repetitions of the oxyalkylene groups in the polyoxyalkylene chain in the side chain of the polymer is not particularly limited, but is preferably 2 to 50, more preferably 3 to 20.
[0139] The weight average molecular weight (Mw) of the polymer having a polyoxyalkylene chain is preferably 1,000 to 150,000, more preferably 10,000 to 100,000.
[0140] The polymer having a polyalkyleneimine chain is a high molecular compound having a polyalkyleneimine chain composed of an amine and an alkylene group in at least one of a main chain and a side chain.
[0141] Examples of the alkylene group constituting the polyalkyleneimine chain include linear or branched alkylene groups having 1 to 6 carbon atoms, preferably ethylene, propylene or butylene, and more preferably ethylene.
[0142] As the polymer having a polyoxyalkylene chain in the main chain, polyethyleneimine obtained by ring-opening polymerization of ethyleneimine is preferred. Examples of polyethyleneimine include linear, branched, and dendrimer forms.
[0143] In the polymer having a polyalkyleneimine chain in a side chain, the structure of the main chain is not particularly limited, and examples thereof include the structure of the main chain of the polymer having a polyoxyalkylene chain in the side chain.
[0144] The number of repetitions of the alkyleneimine groups in the polyalkyleneimine chain present in the side chain of the polymer is not particularly limited, but is preferably 2 to 50, more preferably 3 to 20.
[0145] The weight average molecular weight (Mw) of the polymer having a polyalkyleneimine chain is preferably 1,000 to 150,000, more preferably 10,000 to 100,000.
[0146] The polymer having a cyclic amide group is a high molecular compound having a cyclic amide group in a side chain.
[0147] Examples of the cyclic amide group include groups having a structure derived from N-vinylpyrrolidone and N-vinylcaprolactam.
[0148] Examples of the polymer having a cyclic amide group include copolymers of monomers containing a cyclic amide group such as polyvinyl pyrrolidone, polyvinyl caprolactam, and N-vinyl pyrrolidone and N-vinyl caprolactam with monomers containing a vinyl group such as vinyl acetate. Preferred are copolymers of polyvinyl pyrrolidone, polyvinyl caprolactam or N-vinyl pyrrolidone and vinyl acetate.
[0149] The weight average molecular weight (Mw) of the polymer having a cyclic amide group is preferably 1,000 to 150,000, more preferably 10,000 to 100,000.
[0150] Cellulose acetate is cellulose in which at least a part of hydroxyl groups is substituted with acetyl groups, and examples thereof include cellulose diacetate, cellulose triacetate, and cellulose in which a part of hydroxyl groups is further substituted with acyl groups other than acetyl groups.
[0151] The degree of substitution of the hydroxyl groups in cellulose acetate is not particularly limited, but when the hydroxyl groups of cellulose acetate are substituted only with acetyl groups, the degree of substitution is preferably 1 to 15, and more preferably 2 to 4. Furthermore, when the hydroxyl groups of cellulose acetate are substituted with groups other than acetyl groups, the total degree of substitution is preferably 1 to 50, and more preferably 30 to 50.
[0152] Examples of the acyl group other than the acetyl group which substitutes the hydroxyl group in cellulose acetate include propionyl, butyryl, dodecanoyl, octadecanoyl, tert-butyryl, oleoyl, benzoyl, naphthylcarbonyl and cinnamoyl, and propionyl or butyryl is preferred.
[0153] As the cellulose acetate, cellulose diacetate, cellulose triacetate, cellulose acetate propionate or cellulose acetate butyrate is preferred, and cellulose acetate propionate or cellulose acetate butyrate is more preferred.
[0154] The weight average molecular weight (Mw) of cellulose acetate is preferably 1,000 to 150,000, more preferably 10,000 to 100,000.
[0155] The polymer B1 may be used alone or in combination of two or more.
[0156] The content of the polymer B1 in the polymer layer is not particularly limited, but is preferably 10 to 50% by mass, more preferably 30 to 40% by mass, based on the total mass of the polymer layer, from the viewpoint of achieving more excellent effects of the present invention.
[0157] -Polymer B2-
[0158] The polymer layer preferably contains a polymer B2 having a cross-linked structure in addition to the above-mentioned polymer A.
[0159] The cross-linked structure of the polymer B2 refers to a three-dimensional mesh network structure formed by cross-linking.
[0160] As polymer B2 having a cross-linked structure, for example, there can be mentioned polymers and copolymers obtained by polymerizing a multifunctional polymerizable compound having two or more polymerizable groups, and cross-linked polymers obtained by reacting a polymer having a reactive group obtained by polymerizing a polymerizable compound with a cross-linking agent having two or more cross-linkable groups reactive with the reactive groups.
[0161] The polyfunctional polymerizable compound is not particularly limited as long as it is a monomer or oligomer having two or more polymerizable groups, and examples thereof include polyfunctional free radical polymerizable compounds having two or more free radical polymerizable groups such as (meth)acryloyl, vinyl, styryl and allyl groups.
[0162] Examples of the polyfunctional radical polymerizable compound include polyfunctional (meth)acrylate compounds, polyfunctional vinyl ethers, and polyfunctional allyl compounds, and polyfunctional (meth)acrylate compounds are preferred.
[0163] Examples of the polyfunctional (meth)acrylate compound include 1,6-hexanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, PO-modified neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0164] Examples of the polymer constituting the cross-linked polymer include acrylic resins, polyolefin resins, and polyester resins.
[0165] Examples of the reactive groups possessed by the polymer include hydroxyl groups, amino groups, and carboxyl groups. Examples of the crosslinking agent include compounds having two or more crosslinking groups selected from the group consisting of carboxyl groups, epoxy groups, oxetane groups, and isocyanate groups.
[0166] As a more specific cross-linked polymer, for example, there can be mentioned a cross-linked acrylic resin obtained by reacting an isocyanate cross-linking agent (a compound having two or more isocyanate groups) and / or an epoxy cross-linking agent (a compound having two or more epoxy groups) with an acrylic resin having a group selected from the group consisting of a hydroxyl group and an amino group.
[0167] The polymer B2 may be used alone or in combination of two or more.
[0168] The content of the polymer B2 in the polymer layer is not particularly limited, but is preferably 10 to 50% by mass, more preferably 30 to 40% by mass, based on the total mass of the polymer layer, from the viewpoint of achieving more excellent effects of the present invention.
[0169] <Additives>
[0170] The polymer layer may contain additives other than the above-mentioned polymers.
[0171] Examples of additives that may be contained in the polymer layer include plasticizers, silane coupling agents, and particles.
[0172] (Plasticizer)
[0173] The polymer layer may comprise a plasticizer, preferably comprises a plasticizer.
[0174] By including a plasticizer in the polymer layer, the compatibility of the polymer layer with the sealing liquid (xylene or the like) can be improved, and the dissolution rate of the polymer layer when it comes into contact with a solvent can be increased, or the brittleness of the polymer layer can be improved.
[0175] Examples of the plasticizer include phosphate plasticizers such as triphenyl phosphate, bisphenol A bis-(diphenyl phosphate), trimethyl phosphate, triethyl phosphate, and diphenyl-2-methacryloylethyl ester; adipate plasticizers such as dioctyl adipate, dibutyl adipate, and diisobutyl adipate, and ADEKASIZER LV-808 (manufactured by ADEKA CORPORATION) and POLYSIZER W-242, W-230-H, W-1020-EL, and W-1430-EL; sebacic acid ester plasticizers such as dioctyl sebacate; maleic acid ester plasticizers such as dibutyl maleate; tri(2-ethylhexyl) trimellitate; and triacetin.
[0176] In addition, examples of the plasticizer include phthalate plasticizers such as diethyl phthalate, dioctyl phthalate, dinonyl phthalate, didecyl phthalate, diisononyl phthalate, heneicosyl phthalate, bis(2-ethylhexyl)phthalate, and isodecyl phthalate; trimethylol propionate esters such as ADEKASIZER C series (e.g., C-8, etc., manufactured by ADEKA CORPORATION) and MONOSIZER W-705 (manufactured by DIC CORPORATION); pyromellitic acid ester plasticizers such as ADEKASIZER UL-80 and UL-100 (manufactured by ADEKA CORPORATION); dipentaerythritol esters such as ADEKASIZER UL-8 (manufactured by ADEKA CORPORATION); MONOSIZER W-150 (DIC CORPORATION); Carboxylic acid ester plasticizers having an epoxy group, such as DICCORPORATION; and benzoic acid ester plasticizers, such as MONOSIZER PB-3A (manufactured by DICCORPORATION).
[0177] In addition, plasticizers include deep eutectic solvents (DES). Deep eutectic solvents are solvents containing hydrogen bond acceptor compounds and hydrogen bond donor compounds, and the melting point of the eutectic is lowered significantly by mixing the hydrogen bond acceptor compounds and hydrogen bond donor compounds.
[0178] Examples of hydrogen bond accepting compounds include quaternary ammonium compounds, phosphorus compounds, metal salts, amino acids and polycarboxylic acids, and examples of hydrogen bond donating compounds include alcohol compounds, sugars, carboxylic acids and amine compounds.
[0179] As the deep eutectic solvent, for example, there can be mentioned the compounds described in paragraphs 0025 to 0048 of U.S. Patent Application Publication No. 2018 / 0194913 and JP-A-2020-105336.
[0180] As the plasticizer, a plasticizer having high compatibility with the polymer A contained together with the plasticizer in the polymer layer is preferred. Among them, a plasticizer having a Hansen solubility parameter distance (ΔHSP) of 6 MPa with the polymer A is more preferred. 0.5 The following plasticizers are further preferably 2MPa ΔHSP with polymer A 0.5 The lower limit of the above ΔHSP is not limited and can be 0 MPa 0.5 .
[0181] The plasticizer is preferably a low molecular weight compound. Specifically, the molecular weight of the plasticizer is preferably 100 to 10,000, more preferably 100 or more and less than 1,000.
[0182] In particular, as the plasticizer, a phosphate plasticizer, an adipate plasticizer, a maleate plasticizer, or a phthalate plasticizer is preferred from the viewpoint of more excellent improvement in the brittleness of the polymer layer.
[0183] The plasticizer may be used alone or in combination of two or more.
[0184] When the polymer layer includes a plasticizer, the content of the plasticizer is not particularly limited, and is preferably 0.5% by mass or more, more preferably 1% by mass or more, relative to the total mass of the polymer layer. The upper limit is not particularly limited, and from the viewpoint of the adhesion between the polymer layer and the substrate, it is preferably 20% by mass or less, more preferably 10% by mass or less, relative to the total mass of the polymer.
[0185] (Silane coupling agents)
[0186] The polymer layer may contain at least one selected from the group consisting of a silane coupling agent, a hydrolyzate thereof, and a hydrolysis-condensation product thereof (hereinafter, these may also be collectively referred to as “silane coupling agents”).
[0187] If the polymer layer contains a silane coupling agent, even if the cover film is stored in a roll, adhesion between the polymer layer and the back side of the support (the surface of the support opposite to the surface on which the polymer layer is formed) is less likely to occur, and storage properties over time are better, which is preferred.
[0188] The type of silane coupling agent is not particularly limited, but preferably has two or more different reactive groups in the molecule, at least one of which is a reactive group that chemically bonds to an inorganic substance, and at least one of which is a reactive group that chemically bonds to an organic material.
[0189] It will be readily understood by those skilled in the art that the type of the silane coupling agent used in the polymer layer is appropriately selected depending on the type of the polymer constituting the polymer layer.
[0190] The content of the silane coupling agent in the polymer layer is preferably 0.1 mg / m 2 More preferably, 5 to 25 mg / m 2 .
[0191] (particle)
[0192] The polymer layer may contain particles.
[0193] The type of particles is not particularly limited, and examples thereof include inorganic particles such as silica particles and titania particles, and organic particles composed of polymers such as PMMA, and silica particles are preferred.
[0194] The surfaces of the inorganic particles are preferably subjected to a hydrophobic treatment from the viewpoint of being able to suppress the hydrophilic material from seeping out (migration) from a member in contact with the polymer layer.
[0195] The size of inorganic particles and organic particles is not particularly limited. If too large, scattering is likely to occur, and visibility is sometimes deteriorated. Therefore, the average secondary particle size of inorganic particles and organic particles (the average particle size of the agglomerates of inorganic particles and organic particles) is preferably less than 1 μm. The lower limit is not particularly limited and can be more than 1 nm. In addition, the average secondary particle size of inorganic particles and organic particles can be measured according to dynamic light scattering and using a particle size measuring device (OTSUKA ELECTRONICS CO., LTD manufactures "nanoSAQLA").
[0196] When the polymer layer contains particles, the refractive index of the particles is preferably close to the refractive index of the polymer layer from the viewpoint of preventing scattering. More specifically, the refractive index of the inorganic particles and the organic particles is preferably 1.40 to 1.60.
[0197] When the polymer layer contains particles, the content thereof is, for example, 0.5 to 20% by mass relative to the total mass of the polymer layer.
[0198] <Physical properties of polymer layer>
[0199] (thickness)
[0200] The thickness of the polymer layer is not particularly limited, but is preferably 1 μm or more, more preferably 10 μm or more, from the viewpoint of achieving better adhesion to a substrate such as a slide glass.
[0201] The upper limit is not particularly limited, and is, for example, 100 μm or less, preferably 40 μm or less, and more preferably 30 μm or less.
[0202] (Glass transition temperature (Tg))
[0203] The glass transition temperature Tg of the polymer layer is preferably 35° C. or higher, more preferably 45° C. or higher, from the viewpoint that the viscoelasticity of the polymer layer is reduced to prevent adhesion to other members and the anti-blocking property is further improved.
[0204] The upper limit of the glass transition temperature Tg of the polymer layer is not particularly limited, but is preferably 130° C. or lower from the viewpoint of being able to improve the brittleness of the film.
[0205] The method for measuring the glass transition temperature Tg of the polymer layer is described in Examples below.
[0206] The glass transition temperature Tg of the polymer layer can be adjusted by the type and content ratio of the polymer constituting the polymer layer.
[0207] (Refractive Index)
[0208] From the optical viewpoint of observation under a microscope, the refractive index of the polymer layer is preferably 1.45 to 1.56, which is close to glass (refractive index 1.52 to 1.56), more preferably 1.46 to 1.56, and even more preferably 1.47 to 1.56.
[0209] 〔Other layers〕
[0210] The cover film may have other layers in addition to the support and the polymer layer.
[0211] As another layer, a backing layer can be mentioned.
[0212] The backing layer is provided on the back side of the support (the side opposite to the side provided with the polymer layer) for the purpose of preventing scratches on the surface of the cover film, preventing blocking during storage in a very high temperature environment, and balancing curling of the cover film.
[0213] Examples of the constituent material of the backing layer include synthetic polymers having a high glass transition temperature such as polystyrene and polymethyl methacrylate, and gelatin.
[0214] [Physical properties of coating film]
[0215] <Thickness>
[0216] The thickness of the cover film (the total thickness of the polymer layer and the thickness of the support) is not particularly limited, but from the viewpoint of operability and visibility during microscopic observation, it is preferably 250 μm or less, more preferably 200 μm or less, and further preferably 150 μm or less. As for the lower limit, it is preferably 50 μm or more from the perspective of better handling properties such as bending resistance and sealing properties.
[0217] [Method for producing cover film]
[0218] The method for producing the cover film is not particularly limited as long as it is a method for producing a laminate having at least a support and a polymer layer, but it is preferred that the polymer layer is provided on the surface of the support.
[0219] The method of providing the polymer layer on the surface of the support is not particularly limited, and examples thereof include coating, casting, and transfer by a coater or sprayer, etc. Among them, it is preferred that a coating solution containing a solvent and components of the polymer layer is coated on the support, and then the coating film is dried to form the polymer layer.
[0220] The type of solvent used in the coating solution can be appropriately selected from the viewpoints of the solubility of the constituent components of the polymer layer, the drying speed, and the surface tension. Examples of the solvent used in the coating solution include toluene, methyl acetate, ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, cyclohexanone, tetrahydrofuran, methyl tert-butyl ether, and xylene.
[0221] Furthermore, when a solvent capable of dissolving the surface of the support is used as the solvent used in the coating solution, mixing of the constituent components of the polymer layer and the support at the interface can be promoted, and the adhesion between the polymer layer and the support can be improved.
[0222] From the above viewpoints, the coating liquid used for forming the polymer layer preferably contains a solvent selected from the group consisting of toluene, methyl acetate, ethyl acetate, butyl acetate, acetone and methyl ethyl ketone, and more preferably contains at least one solvent selected from the group consisting of toluene, ethyl acetate and acetone.
[0223] From the viewpoint of facilitating control of the surface structure of the polymer layer, the solvent used for forming the polymer layer is preferably a mixture of two or more different solvents.
[0224] The content of the solvent selected from the group consisting of ethyl acetate and butyl acetate in the coating liquid is not particularly limited, and is preferably 40% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more relative to the total mass of the solvent contained in the coating liquid. The upper limit is not particularly limited and may be 100% by mass or less, but is preferably 90% by mass or less.
[0225] As the coating liquid for forming the polymer layer, for example, there can be mentioned a mixed liquid containing at least a solvent and the components constituting the above-mentioned polymer layer. In addition, as the material for forming the polymer layer, a mixed liquid containing monomers that become raw materials of the polymer can be used instead of part or all of the polymer, and after forming a coating film on the support, the monomers are polymerized to form a polymer layer containing the polymer.
[0226] When the coating liquid contains the above-mentioned raw material monomers, the coating liquid preferably contains various polymerization initiators. Examples of the polymerization initiator include photopolymerization initiators and thermal polymerization initiators, and the initiator can be appropriately selected according to the type of the raw material monomers.
[0227] Furthermore, when forming a polymer layer containing the polymer B2 having a crosslinked structure, the coating solution may contain a crosslinking agent as needed. The crosslinking agent can be appropriately selected according to the type of the polymer forming the crosslinked structure and its raw material monomer.
[0228] It is preferable to perform a drying step in which, after the coating liquid is applied onto the support to form a coating film, the obtained coating film is dried to remove the solvent from the coating film.
[0229] As the drying treatment performed in the drying step, there can be mentioned a method of leaving the coating film at room temperature (23° C.) for a predetermined time (e.g., natural drying), air drying by blowing gas to the coating film, heating drying by heating the coating film or the support using a heating member such as an oven, a heating plate, and a heating roller, and a combination thereof. As the drying step, it is preferred to perform at least one of air drying and heating drying, and it is more preferred to perform air drying and heating drying in combination.
[0230] The temperature of the gas used in air drying is not particularly limited, but is preferably 50 to 160° C., more preferably 80 to 140° C. Examples of the gas used in air drying include air and nitrogen.
[0231] The temperature of the heating and drying using the heating means is not particularly limited, but is preferably 50 to 160° C. The heating time is preferably 0.5 to 20 minutes.
[0232] 〔use〕
[0233] The cover film of the present invention can be preferably used as a cover film for covering an object to be measured on a substrate, and more preferably used for preparing a specimen for microscopic observation, and more preferably suitable for a microscope having an automatic sealing device.
[0234] The use of the cover film of the present invention is not limited to the above-mentioned uses, and can be used, for example, for thin film sealing on a substrate, and for lower layer protection based on lamination, etc. In addition, the substrate to which the cover film is attached can be glass or a film-shaped substrate (resin, etc.).
[0235] Example
[0236] The present invention is further described in detail below by enumerating examples. The materials, usage amounts, ratios, processing contents, processing sequences, etc. shown in the following examples can be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.
[0237] In addition, "part" and "%" are based on mass unless otherwise specified.
[0238] [Example 1]
[0239] <Preparation of coating solution>
[0240] A polymer (polymer A-1) having a weight average molecular weight of 100,000 and containing repeating units based on ethyl acrylate, repeating units based on methyl methacrylate, and repeating units based on ethyl methacrylate at a mass ratio of 25 / 50 / 25, respectively, was synthesized by solution polymerization.
[0241] The polymer A-1 (16 parts) and the component B1 (9 parts) described later were dissolved in a mixed solvent consisting of toluene (19 parts) and ethyl acetate (56 parts) to obtain a polymer layer-forming coating liquid 1. The composition of the polymer was determined by 1 The results were confirmed by H-NMR (nuclear magnetic resonance).
[0242] <Production of support body>
[0243] (Preparation of Cellulose Ester Solution A1)
[0244] The following ingredients were placed in a mixing tank and stirred while heating to dissolve the ingredients, thereby preparing a cellulose ester solution A1.
[0245] · Cellulose triacetate derived from wood pulp (acetyl substitution degree 2.86, viscosity average polymerization degree 310): 100 parts by mass
[0246] A sugar ester mixture prepared by mixing a mixture of the following sugar ester compounds (I) and (II) and the following sugar ester compound (III) at a mass ratio of 12:3 (mixture of sugar ester compounds (I) and (II): sugar ester compound (III))
[0247] Dichloromethane: 384 parts by mass
[0248] Methanol: 69 parts by mass
[0249] Butanol: 9 parts by mass
[0250] The amount of the sugar ester mixture contained in the cellulose ester solution A1 was adjusted so that the content of the sugar ester mixture contained in the support A1 prepared using the cellulose ester solution A1 (the total content of the sugar ester compounds) became 12.3% by mass.
[0251] The mixture of the sugar ester compounds (I) and (II) is represented by the following general formula (I) and (II), wherein G represents a sucrose residue, and the substituent LR 1 A mixture of aromatic sugar ester compounds representing benzoyl groups, wherein the average degree of substitution (average value of n and q) of sugar ester compounds (I) and (II) is 5.7.
[0252] (I)(HO)m -G-(LR 1 ) n
[0253] (II)(HO) p -G-(LR 1 ) q
[0254] Furthermore, the sugar ester compound (III) is an aliphatic sugar ester compound, and the aliphatic sugar ester compound is represented by the following general formula (III), wherein G' represents a sucrose residue, and the substituent L'-R 2 represents either an acetyl group or an isobutyryl group, and is obtained by replacing an average of 2 hydroxyl groups with acetyl groups and replacing an average of 6 hydroxyl groups with isobutyryl groups among 8 hydroxyl groups of a sucrose residue.
[0255] (III)(HO) t -G'-(L'-R 2 ) r
[0256] (Preparation of Matting Agent Dispersion Liquid B1)
[0257] The following components were placed in a disperser and stirred to dissolve the components, thereby preparing a matting agent dispersion B1.
[0258] Silica particle dispersion (average particle size 16 nm, "AEROSIL R972", manufactured by NIPPON AEROSIL CO., LTD.): 10.0 parts by mass
[0259] Dichloromethane: 72.8 parts by mass
[0260] Methanol: 3.9 parts by mass
[0261] Butanol: 0.5 parts by mass
[0262] Cellulose ester solution A1: 10.3 parts by mass
[0263] The matting agent dispersion B1 was added to the cellulose ester solution A1, and the mixture was heated and stirred sufficiently to dissolve the components to prepare a dope A1. The mixing ratio of the cellulose ester solution A1 and the matting agent dispersion B1 was adjusted so that the total content of the sugar ester compounds of formulas (I) to (III) contained in the support A1 prepared using the dope A1 was 12.3% by mass.
[0264] (Formation of Support A1)
[0265] The obtained dope A1 was heated to 30°C and cast onto a mirror-finished stainless steel drum with a diameter of 3 m through a casting die. The surface temperature of the drum was set to -5°C, and the coating width was set to 1470 mm. The space temperature of the entire casting section was set to 15°C. Then, the triacetyl cellulose film formed on the drum surface was peeled off from the drum just before 50 cm from the end point of the casting section, and the two ends of the peeled triacetyl cellulose film in the width direction were clamped by a pin tenter.
[0266] The triacetyl cellulose web held by the pin tenter was conveyed to a drying zone. Dry air at 45° C. was blown during initial drying. Next, the web was dried by heating at 110° C. for 13 minutes and further at 140° C. for 25 minutes to obtain a transparent triacetyl cellulose film derived from wood pulp having a thickness of 118 μm, i.e., support A1.
[0267] <Production of Cover Film>
[0268] The coating liquid 1 was applied to the support A1 in an amount such that the solid content film thickness (the thickness of the polymer layer after drying) became 19 μm. Then, the coating film formed on the support A1 was dried for 2 minutes in an environment with a wind speed of 3.2 m / s and 100° C., and further dried in an oven at 100° C. for 10 minutes to obtain a cover film 1 having the support A1 and the polymer layer.
[0269] [Example 2 to Example 10, Comparative Example 1 to Comparative Example 3]
[0270] Cover films of Examples 2 to 10 and Comparative Examples 1 to 3 were produced according to the method described in Example 1, except that coating solutions having compositions described in Table 1 described later were used as the polymer layer-forming coating solutions.
[0271] In Example 8, after the coating film formed on the cellulose triacetate film was dried according to the method described in Example 1, the dried coating film was irradiated with ultraviolet rays (irradiation amount 1000 mJ / cm 2 ). Thus, a polymer layer containing a polymer (polymer B2 having a cross-linked structure) which is a polymer of a bifunctional monomer of the following component B-6 is formed.
[0272] The components used to prepare the coating solution are shown below.
[0273] (Polymer A)
[0274] Polymer A-2: "UR-1400" manufactured by TOYOBO CO., LTD., polyester resin, number average molecular weight 40,000, Tg about 83°C
[0275] (ingredient B)
[0276] Component B-1: "Hydromed D4" manufactured by AdvanSource, a polyurethane having a polybutene oxide segment, Tg of about 30°C.
[0277] Component B-2: "Hydromed D640" manufactured by AdvanSource, a polyurethane containing a polybutene oxide segment, Tg of about 50°C.
[0278] Component B-3: "CAB-551-0.2" manufactured by Eastman Co., Ltd., cellulose acetate butyrate, weight average molecular weight: 30,000, Tg: 101°C.
[0279] Component B-4: "CAP-482-0.5" manufactured by Eastman Co., Ltd., cellulose acetate propionate, weight average molecular weight: 25,000, Tg: 142°C.
[0280] Component B-5: "PVP / VA S-630" manufactured by Ashland Japan Co. Ltd., a copolymer of polyvinyl pyrrolidone / vinyl acetate, weight average molecular weight 51,000, Tg 110°C.
[0281] Component B-6: "TPGDA" manufactured by Daicel Corporation, tripropylene glycol diacrylate
[0282] (additive)
[0283] Photopolymerization initiator: IRGACURE 907, MMMP (2-methyl-1 (4-methylthiophenyl)-2-morpholinopropane-1-one)
[0284] Plasticizer: dibutyl maleate
[0285] [Comparative Example 4]
[0286] <Formation of Support A2>
[0287] (Preparation of Core Layer Cellulose Acylate Dopant)
[0288] The following composition was placed in a mixing tank and stirred to dissolve the components to prepare a cellulose acetate solution used as a doping agent for the core layer cellulose acylate.
[0289] The composition of the core layer cellulose acylate dopant is shown below.
[0290] · Cotton linter-derived cellulose triacetate (acetyl substitution degree 2.88): 100 parts by mass
[0291] Polyester A: 12 parts by mass
[0292] Polarizer durability improver (A-3): 2 parts by mass
[0293] Dichloromethane: 430 parts by mass
[0294] Methanol: 64 parts by mass
[0295] Polyester A is a condensate of 1,2-cyclohexyldicarboxylic acid and ethylene glycol, and has a terminal structure in which hydrogen atoms of hydroxyl groups at both terminals of the polyester are substituted (sealed) with cyclohexanoyl groups. The number average molecular weight of Polyester A is 850.
[0296] The polarizer durability improver (A-3) is a compound represented by the following structural formula.
[0297] [Chemical formula 1]
[0298]
[0299] (Preparation of outer layer cellulose acylate dopant)
[0300] To 90 parts by mass of the core layer cellulose acylate dopant was added 10 parts by mass of the following matting agent solution to prepare a cellulose acetate solution as the outer layer cellulose acylate dopant.
[0301] The composition of the matting agent solution is shown below.
[0302] Silica particles with an average particle size of 20 nm (AEROSIL R972, manufactured by NIPPON AEROSIL CO., LTD.): 2 parts by mass
[0303] Dichloromethane: 76 parts by mass
[0304] Methanol: 11 parts by mass
[0305] Core layer cellulose acylate dopant: 1 part by mass
[0306] (Formation of Support Body A2)
[0307] After filtering the core layer cellulose acylate dopant and the outer layer cellulose acylate dopant using filter paper having an average pore size of 34 μm and a sintered metal filter having an average pore size of 10 μm, the core layer cellulose acylate dopant and the outer layer cellulose acylate dopant disposed on both sides thereof, a total of three layers, were simultaneously cast from a casting port onto a drum at 20° C. (belt casting machine). Next, the laminated film was peeled off from the support, and both ends of the film in the width direction were fixed with a tenter clamp, and dried while being stretched in the transverse direction at a stretching ratio of 1.1 times. Then, the film was further dried by conveying between rollers of a heat treatment device, thereby obtaining a transparent triacetate cellulose film derived from cotton wool having a thickness of 118 μm, namely, the support A2.
[0308] <Production of Cover Film>
[0309] A cover film of Comparative Example 4 was produced according to the method described in Example 1 above, except that Support A2 was used instead of Support A1.
[0310] [Measurement of physical properties of coating film]
[0311] [Glass transition temperature (Tg) of polymer layer]
[0312] The polymer layer was peeled off from the covering film produced in each example. The obtained polymer layer was cut into a size of 5 mm×30 mm to obtain a sample A of the polymer layer. The obtained sample A was humidified for more than 2 hours at 25°C and a relative humidity of 60%. Then, using a dynamic viscoelasticity measuring device (Vibron: DVA-225 (manufactured by IT Keisoku Seigyo Co., Ltd.)), the peak temperature of the loss tangent (loss elastic modulus / storage modulus) of sample A observed when the temperature was increased from 30°C under the conditions of a clamping distance of 20 mm, a heating rate of 5°C / min and a frequency of 100 Hz was measured, and the glass transition temperature Tg (°C) of sample A was obtained.
[0313] 〔Xylene Residual Rate〕
[0314] The coating liquid for forming a polymer layer was applied to the support in an amount such that the solid content film thickness (thickness of the polymer layer after drying) became 40 μm, and a cover film for evaluating the residual xylene rate was prepared according to the methods described in Examples 1 to 10 and Comparative Examples 1 to 4. The polymer layer was peeled off from the prepared cover film, and the polymer layer was cut to an area equivalent to a circle with a diameter of 20 mm, thereby obtaining a sample B of a polymer layer with a film thickness of 40 μm.
[0315] Sample B is placed in a bag-shaped metal mesh made of stainless steel, and the metal mesh containing sample B is placed in a beaker with a capacity of 5 mL. 2 g of xylene is placed in the beaker, and sample B is immersed in xylene. During the immersion, sample B is arranged in a manner that sample B does not appear from the liquid surface of xylene. The temperature of xylene and sample B in the immersion test is 25°C. After immersing sample B in xylene for more than 4 hours, the metal mesh containing the residue of sample B is taken out. The residue together with the metal mesh is dried until the weight no longer decreases to remove the xylene. The weight of the residue after drying is measured, and the xylene residual rate (mass %) is calculated by the following formula based on the weight of the obtained residue and the weight of sample B measured before immersion.
[0316] Xylene residual rate = {(weight of sample B before immersion - weight of residue after immersion) / weight of sample B before immersion} × 100
[0317] [Evaluation of Cover Film]
[0318] 〔Storage over time〕
[0319] The cover film prepared in each example and each comparative example was bonded to a slide glass using a Cover Aid automatic sealing device (manufactured by SAKURA SEIKI CO., LTD., "SCA-Film-J0") to prepare a sample of a bonded body. Xylene was used as a sealing solvent.
[0320] The obtained samples were left to stand for 7 days in an environment of 40°C and 80% RH, and an accelerated test was performed. The cover film of the sample after the accelerated test was observed with the naked eye, and the storage properties over time were evaluated according to the following criteria based on the degree of increase in the area of bubbles and peeling generated parts with a size of 1 mmφ or more compared to the cover film of the sample before the accelerated test. In addition, in the following evaluation, if it is 1 to 3, it is a level that is not a problem in practical use.
[0321] (Evaluation criteria for long-term storage performance)
[0322] 1: No increase in bubbles or peeling was observed.
[0323] 2: An increase in either bubbles or peeling is observed, the increase in bubbles is less than 2, and the increase in the area of the peeling-occurring portion is less than 5% relative to the total area of the cover film.
[0324] 3: The number of bubbles increased by 2 or more and less than 4, and / or the increase in the area of the peeling-occurring portion was 5% or more and less than 10% relative to the total area of the cover film. In addition, it does not belong to the following evaluation 4.
[0325] 4: The number of bubbles increased by 4 or more, and / or the area of the peeling-occurring portion increased by 10% or more relative to the total area of the cover film.
[0326] Table 1 shows the constituent materials of the support, the composition of the coating solution for forming the polymer layer, the physical properties of the polymer layer, and the evaluation results.
[0327] In the following tables, the "Raw Material" column of "Support" indicates the raw material of the constituent material of the support.
[0328] Each column of "coating liquid" shows the components contained in the coating liquid for forming a polymer layer used in each example.
[0329] The "ΔHSP" column of "Component B" shows the Hansen solubility parameter distance (unit: MPa) between the polymer used as component B in each example and xylene, calculated by the above method. 0.5 ).
[0330]
[0331] The results shown in the table confirm that the cover film of the present invention has a superior effect to the cover films of Comparative Examples 1 to 4 in which the support does not include cellulose triacetate or a polymer layer derived from wood pulp and the residual xylene ratio is less than 10% by mass or more than 50% by mass.
[0332] It was confirmed that the effect of the present invention is more excellent when the polymer contained in the polymer layer contains an acrylic resin having two or more repeating units derived from monomers selected from the group consisting of acrylic acid ester monomers and methacrylic acid ester monomers (comparison between Examples 1 and 10).
[0333] It was confirmed that the effect of the present invention is more excellent when the polymer contained in the polymer layer contains a polymer having a ΔHSP with xylene of 8 or more (comparison between Examples 1 to 4 and Example 7).
[0334] It was confirmed that the effect of the present invention is more excellent when the residual xylene ratio of the polymer layer is 40% by mass or less, and the effect of the present invention is more excellent when the residual xylene ratio of the polymer layer is 28 to 37% by mass (comparison of Examples 1 to 9).
Claims
1. A covering film comprising a support and a polymer layer comprising a polymer, The support comprises cellulose triacetate derived from wood pulp, The polymer layer satisfies the following requirement 1: Requirement 1: The remaining ratio of the polymer layer peeled from the cover film before and after being immersed in xylene at 25° C. is 10 to 50% by mass.
2. The covering film according to claim 1, wherein The polymer includes a polymer A, and the polymer A is at least one selected from the group consisting of acrylic resins and polyester resins.
3. The covering film according to claim 1, wherein: The polymer includes an acrylic resin having two or more repeating units derived from monomers selected from the group consisting of acrylic acid ester monomers and methacrylic acid ester monomers.
4. The covering film according to claim 2, wherein: The acrylic resin has a weight average molecular weight of 50,000 to 150,000.
5. The covering film according to claim 1, wherein The glass transition temperature of the polymer layer is 35° C. or higher.
6. The covering film according to any one of claims 1 to 5, wherein The polymer comprises a Hansen solubility parameter distance to xylene of 8 MPa 0.5 Polymer B1 above.
7. The covering film according to claim 6, wherein: The polymer B1 includes at least one selected from the group consisting of a polymer having a polyoxyalkylene chain, a polymer having a polyalkyleneimine chain, a polymer having a cyclic amide group, and cellulose acetate.
8. The covering film according to any one of claims 1 to 5, wherein The polymer includes a polymer B2 having a cross-linked structure.
9. The covering film according to any one of claims 1 to 5, wherein The polymer layer also includes a plasticizer.
10. The covering film according to any one of claims 1 to 5, which is used to cover an object to be measured on a substrate during microscopic observation.
Citation Information
Patent Citations
Sample exchanging device for scan type electron microscope or the like
JP1988250048A
Cellulose ester or film of the same, and method for producing the same
JP2005082744A
Thermoplastic resin composition and molding obtained by molding the same
JP2020105336A
Highly transparent coated cellulose triacetate film and dissolver medium
US10988590B2
Highly transparent coated cellulose triacetate film and dissolver medium
US20180194913A1